Peripartum Cardiomyopathy: Management Strategies for Pregnancy Termination - Ashley M. Darlington; Jonah D. Fleisher; Joan E. Briller (Mary Ann Liebert, 2020)
Some women have underlying cardiovascular disease that leads to increased morbidity and mortality with pregnancy. These women may choose to terminate a pregnancy rather than face this increased risk. The optimal approach for pregnancy termination in women with cardiomyopathy is not well defined. We present two women with peripartum cardiomyopathy, both modified World Health Organization (mWHO) class IV and with elevated Cardiac Disease in Pregnancy (CARPREG II) pregnancy risk stratification scores who are at the highest risk for pregnancy continuation. Both underwent induced abortion, although the procedure was performed in very different settings. These cases illustrate factors that influence the mode and setting of pregnancy termination performance.